Pelatihan Mahasiswa dalam Pemanfaatan Sampah Kering Menjadi Briket Biomassa: Solusi Pengelolaan Sampah dan Sumber Energi Alternatif - Mukhtar Galib; Maulana Maulana; Arif Mashuri; Muhammad Basri; Andi Ardasanti (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This community engagement project trained students in utilizing dry waste to produce biomass briquettes, equipping them with essential skills for their future community service (KKN) activities. The training, attended by 20 students, covered theoretical and practical aspects, including waste management, biomass briquette concepts, and alternative energy sources. Lectures and presentations by experts provided a comprehensive understanding of biomass briquettes. Practical demonstrations taught students the steps involved in briquette production, from waste collection and processing to mixing and using natural adhesives. The training also included marketing strategies, market analysis, and business model development to equip students with entrepreneurial skills. Results indicated high levels of understanding and skill acquisition, with 90% successfully performing drying and crushing techniques, 85% correctly mixing materials and adhesives, and 80% effectively conducting quality tests on briquettes. The training significantly improved participants' teamwork and communication skills, essential for their upcoming KKN activities. This project contributed to sustainable waste management practices and alternative energy solutions, enhancing students' readiness to implement these practices in their communities.